The Benthic Invertebrates Floodplain Index – Extending the assessment approach. (August 2017) - Funk, Andrea; Trauner, Daniel; Reckendorfer, Walter; Hein, Thomas
Highlights: An index to assess the ecological status of floodplain systems, the "Benthic Invertebrate Floodplain Index" (BIFI), is developed. The inclusion of abundant and species rich taxa improves the robustness of the index with a low sampling effort. The so far published indices are extended to a better coverage of dynamic water bodies. Abstract: Floodplains are highly diverse landscape elements within river systems and among the most endangered ecosystems worldwide. In this paper we complement indices developed to assess the ecological status of floodplain systems, compliant with the EU Water Framework Directive, to an overall "Benthic Invertebrate Floodplain Index" (BIFI). With the addition of taxa (mainly oligochaetes, chironomidae and amphipoda) to the floodplain index (FI), caddisfly (CHI), and dragon fly (OHI) indices a new extended BIFI can be calculated. We provide values for the calculation of the index derived from a comprehensive dataset of Austrian floodplain waters complemented by literature data. Values are given for those taxonomic groups which are abundant in the Austrian Danube and determinable in reasonable time. The new index was compared to published floodplain indices and tested with an independent data set at two floodplain segments along the Austrian Danube. The newly classified benthic invertebrates (NCBI) showed a good performance in comparison to the so far published indices and extend these to a better coverage of dynamic water bodies. Further the inclusion of abundant and species rich taxa improves the robustness of calculated values already with a low sampling effort. Altogether it is a promising tool for the integrated assessment of the ecological status of river-floodplain systems according to the EU Water Framework Directive.